2022
DOI: 10.18502/ijm.v14i4.10246
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study and antifungal susceptibility profile of Trichophyton rubrum and Trichophyton mentagrophytes strains isolated from lesions of humans and cattle

Abstract: Background and Objectives: Monitoring of contagious diseases is important to advance our knowledge of their epidemi- ology and to enable more impressive investigation and prevention efforts. This study aimed to examine antifungal drug sus- ceptibility and molecular analysis of clinical isolates of Trichophyton rubrum and Trichophyton mentagrophytes in humans and cattle. Materials and Methods: A total of 400 patients and 500 cattle were evaluated in this study. Dermatophytosis was confirmed in cases by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
0
0
1
Order By: Relevance
“…ochraceum, in which ERG3 and ERG6 were not detected. This result is similar to that of a previous study (29), which reported that strains with polymorphic ERG genes are resistant to drugs, whereas strains without this gene family are sensitive to all antifungals.…”
Section: Discussionsupporting
confidence: 92%
“…ochraceum, in which ERG3 and ERG6 were not detected. This result is similar to that of a previous study (29), which reported that strains with polymorphic ERG genes are resistant to drugs, whereas strains without this gene family are sensitive to all antifungals.…”
Section: Discussionsupporting
confidence: 92%
“…O tratamento das infecções por T. rubrum é desafiador, porque apenas algumas opções terapêuticas, como azóis e alilaminas que interferem na via de biossíntese do ergosterol, estão disponíveis (Li et al, 2021). Além disso, o tratamento é longo e caro e vários casos de resistência antifúngica vem sendo relatados (Perlin et al, 2017;Khan et al, 2022;Mohammadifard et al, 2022;Branco et al, 2023;Martinez-Rossi et al 2021).…”
Section: Tratamento Das Infecções Fúngicasunclassified